A color of his own - Lionni, Leo, 1910- (New York : A. Knopf, 1997)
A little chameleon is distressed that he doesn't have his own color like other animals.
"Dragonfly Books"
Originally published: Great Britain : Abelard-Schuman, 1975.
Elem. School Library Collection
Booklist
Horn Book
Lexile 640
Keywords: Chameleons -- Juvenile fiction; Chameleons -- Fiction